Professional Talk Series Webinar UMP - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 19 August 2021 - A Professional Talk on Navigating Academia towards IP Commercialization and Research Grants availability in Malaysia was conducted on 19 August 2021, as an implementation towards FK’s External research grant strategic plan.